Modeling and Analysis of the Effect of Dip-Spin Coating Process Parameters on Coating Thickness Using Factorial Design Method - Sorasutee Buapool; Nandh Thavarungkul; Nakorn Srisukhumbowornchai; Preecha Termsuksawad (Advances in Materials Science and Engineering)
Statistical modeling of the dip-spin coating process to describe colloidal PTFE dispersion coating on the external surface of a small diameter hollow tube was developed by using 24 factorial design with a center point to predict the coating thickness in a range of 4–10 μm. The coating parameters included viscosity, withdrawal rate, spin speed, and immersion time. The adequacy of the predicted model was verified by coefficients of determination and lack-of-fit test. Model accuracy was verified by comparing predicted values with experimental results. The significant interaction effects on the coating thickness were three-way interaction among withdrawal rate, spin speed, and immersion time and two-way interactions between viscosity and withdrawal rate, viscosity and spin speed, and viscosity and immersion time. Cube plot for coating thickness reveals a trend of increasing coating thickness towards high levels of viscosity, withdrawal rate, and immersion time and lower level of spin speed.